"¡Mi patria en llamas será mi hoguera!": El fuego y su simbología en Troyanas de Eurípides y la puesta en escena de Szuchmacher (Buenos Aires, 2005) - Rodríguez, Elsa (2020)
This paper aims to analyze the image of fire and its symbolism in two creative interventions about the fall of Troy: Euripides’ Trojan Women (Athens, 415 B.C.) and its staging by Szuchmacher (Buenos Aires, 2005). In the Greek tragedy we witness the last day of Troy: the city has been sacked; the men, dead; the women, raffled as slaves for the victors. The fire will configure a key element of destruction inasmuch as the very city is burned as the last victim in its funeral pyre. In the Buenos Aires version, the Trojan women appear seated at desks, passively watching TVs lit with scenes from the Iraq War that will continue to be projected throughout the whole play. The desks are vintage and refer us to a large office where a bureaucracy seems to have been installed, probably a reference to the ruin of the State and suggestive indication of the relevance of media in that situation. Burning a city on stage as closing of a play is, on the one hand, a singular fact in the classic tragedy but, on the other, it also implies a challenge for performance in both classical and contemporary theatre.